A Cu-BDC@CF catalyst and its preparation method and application

By developing Cu-BDC@CF catalysts, the production of nitric oxide in medical catheters using heterogeneous electrocatalytic technology is solved, and the risk of catheter infection and thrombosis is achieved is achieved with low cost, efficient and recyclable catalytic effects.

CN116351474BActive Publication Date: 2025-04-08TIANJIN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310210811.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-07
Publication Date
2025-04-08
Estimated Expiration
2043-03-07

AI Technical Summary

Technical Problem

The prior art has high costs, instability and difficulty in catalyst recovery and separation in solving the risks of blood flow infection and thrombosis associated with medical catheters.

Method used

A Cu-BDC@CF catalyst is developed, which consists of Cu-MOFs and carbon fibers. It can reduce nitrites in medical catheters through heterogeneous electrocatalytic technology to generate nitric oxide, which is low-cost, efficient, stable and recyclable.

Benefits of technology

The efficient and controllable production of nitric oxide in medical catheters is achieved, reducing the risk of catheter infection and thrombosis, and the recycling and reuse of catalysts simplifies the process and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116351474B_ABST
    Figure CN116351474B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of materials and relates to a Cu‑BDC@CF catalyst and a preparation method and application thereof. The present invention uses a hydrothermal synthesis method to prepare Cu‑BDC powder, and then combines the Cu‑BDC powder with carbon fiber to prepare a Cu‑BDC@CF catalyst. The catalyst utilizes the heating physical properties and mechanical strength of the base carbon fiber to realize the combination of heterogeneous electrocatalytic nitrite generation NO technology and medical catheters, and has the characteristics of low cost, high stability, and recyclability. At the same time, it exhibits effective and controllable catalytic performance for the generation of NO, and the NO flux generated can meet clinical needs. In addition, the preparation method of the Cu‑BDC@CF catalyst of the present invention is simple, does not require complex equipment, and has good commercial prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of materials and relates to a Cu-BDC@CF catalyst and a preparation method and application thereof. Background Art

[0002] In modern medicine, blood catheters are widely used, such as interventional therapy, hemodynamic monitoring, intravenous anesthesia, nutritional support, etc. However, the associated risk of catheter-related bloodstream infection (CRBSI) and thrombosis limits its further application. Currently, many studies have shown that nitric oxide (NO) has some important physiological functions, including its unique vasodilatory properties, anticancer efficacy, antiplatelet activity and antimicrobial / antiviral activity, and can also be used to address the potential risks of CRBSI and thrombosis.

[0003] The key to endowing medical catheters with antibacterial function is to release the antibacterial agent stably, controllably and efficiently within the acceptable flux range of the human body (0.5-4.0 × 10 -10 mol min -1 cm -2 NO) is produced by the production of NO. Currently, there are some strategies to combine NO with medical catheters, giving them the ability to generate NO in situ in the blood or other parts. For example, expensive organic coatings (such as S-nitrosothiol, etc.) are used to coat the walls of blood catheters to slowly release NO, but their high manufacturing costs increase the economic burden on patients. In addition, the use of low-cost nitrite as a NO donor using homogeneous electrocatalysis can achieve controllable generation of NO, but this technology still has great difficulties in the subsequent recovery and separation of the catalyst.

[0004] Heterogeneous electrocatalysis has unique advantages in the field of catalyst recovery and separation. The strategy of developing an easily recyclable heterogeneous electrocatalyst for the in-situ generation of NO by electroreduction of nitrite in medical catheters has become a cheap and controllable technology. The key to using heterogeneous electrocatalysis is to develop a low-cost, efficient and highly stable catalyst. Summary of the invention

[0005] In view of the above problems, the present invention aims to provide a Cu-BDC@CF catalyst and a preparation method thereof, which can be applied in the medical field and solve the problems related to catheter infection.

[0006] Metal-organic framework compounds (MOFs) are a new type of porous organic materials that have developed rapidly in the past two decades. The characteristics of the metal-organic framework structure and its compounds are that it is mainly composed of inorganic metal crystals connected to various metal bridge segments through metal ion centers (sometimes also called various metal-organic crystal ions or metal clusters) and organic ligands connected to various metal bridge segments through mechanical automated processing and assembly to form a type of holistic and long-periodic porous network composite materials. Compared with traditional heterogeneous catalysts (such as zeolites, SiO2, activated carbon, etc.), MOFs have many obvious advantages: high porosity and specific surface area, ordered adjustable channels, customizable and accessible active sites, and post-synthetic modification (PSM), making MOF a promising platform for heterogeneous catalysis research according to the principles of "green chemistry". Therefore, the use of MOF as a heterogeneous catalyst has recently become a research hotspot.

[0007] Based on the MOF material, the present invention combines the strategy of heterogeneous electrocatalytic NO generation with medical catheters, so that the catheters exhibit excellent antibacterial characteristics. The catalyst has the characteristics of low cost, high efficiency, high stability, and recyclability.

[0008] The enzymes that catalyze the production of NO in organisms in nature are complex complexes with Cu as the active center. Therefore, the design of Cu-MOFs with Cu as the ligand center is expected to become an efficient catalyst for the electrocatalytic conversion of NO2 to NO.

[0009] To achieve the above object, the first aspect of the present invention provides a Cu-BDC@CF catalyst, which is mainly prepared by the following method:

[0010] The carbon fiber is immersed in a mixed solution of Cu-BDC and Nafion for 10 to 30 minutes, and then the immersed part is dried to obtain a Cu-BDC@CF catalyst; wherein the concentration of Cu-BDC is 1 to 4 mg / mL, and the concentration of Nafion is 20 to 80 μL / mL.

[0011] Drying methods include but are not limited to air drying, drying under infrared lamps, vacuum drying, microwave drying, etc.

[0012] Furthermore, the soaking and drying are performed ≥ 1 times.

[0013] In the technical solution of the present invention, the Cu-BDC solution is obtained by dissolving Cu-BDC powder in a solvent;

[0014] In a preferred embodiment, the solvent is selected from water, anhydrous ethanol, a mixture of water and ethanol, methanol, and acetonitrile, preferably, anhydrous ethanol.

[0015] Furthermore, Cu-BDC powder is prepared by the following method: the terephthalic acid solution is transferred to a hydrothermal reactor, and then the copper salt solution is spread on the upper layer of the terephthalic acid solution and heated to obtain a blue precipitate, which is then washed and dried.

[0016] In the technical solution of the present invention, the heating conditions are 100-130° C. for 30-40 hours; further, the obtained blue precipitate is washed with DMF and ethanol in sequence.

[0017] Furthermore, the copper salt is one or more of Cu(NO3)2·3H2O, CuSO4·5H2O, and copper chloride.

[0018] In the technical solution of the present invention, the concentration of copper salt in the mixed solution is 4.0×10 -2 ~7.0×10 -2 mmol / mL;

[0019] Furthermore, the copper salt concentration is 4.12×10 -2 ~6.54×10 -2 mmol / mL.

[0020] In the technical solution of the present invention, the concentration of terephthalic acid in the mixed solution is 4.0×10 -2 ~7.0×10 - 2 mmol / mL;

[0021] Furthermore, the concentration of terephthalic acid is 4.12×10 -2 ~6.54×10 -2 mmol / mL.

[0022] In the technical solution of the present invention, the molar ratio of copper salt to terephthalic acid is 1:1.

[0023] In the technical solution of the present invention, the carbon fiber can be carbon fiber filaments or carbon fiber cloth, and the carbon fiber cleaning treatment is specifically as follows: the carbon fiber cloth is ultrasonically placed in a 0.1 mol / L hydrochloric acid solution, then ultrasonically placed in acetone, and finally cleaned with distilled water and / or ethanol.

[0024] Furthermore, when the carbon fiber is a carbon fiber cloth, the specification is (0.5-2) cm×(0.5-2) cm.

[0025] In a specific embodiment of the present invention, the carbon fiber cloth has a size of 1 cm×1 cm.

[0026] Furthermore, the ultrasonic power is 100-400 W, and the ultrasonic time is 0.5-5 min. In a specific embodiment of the present invention, the ultrasonic power is 200 W, and the ultrasonic time is 2 min.

[0027] The second aspect of the present invention provides a use of the Cu-BDC@CF catalyst prepared by the above method in preparing NO by electrocatalytic reduction reaction.

[0028] The third aspect of the present invention provides an application of the Cu-BDC@CF catalyst prepared by the above method in the preparation of medical antibacterial materials; further, the material is a silicone catheter for medical use.

[0029] The application method of the Cu-BDC@CF catalyst in a medical antibacterial catheter is as follows:

[0030] Electrolyte configuration:

[0031] Weigh a certain amount of sodium nitrite, 3-(N-morpholine) propanesulfonic acid, sodium 3-(N-morpholine) propanesulfonate, and sodium chloride, and dissolve them in deionized water to form a clear and transparent solution, the concentration of each component of which is 0.4-0.6M NaNO2, 0.5M MOPS buffer, and 0.2-0.4M NaCl. Preferably, 0.4M NaNO2 and 0.2M NaCl. NaNO2 is used as a NO donor to be electroreduced to NO and released to the relevant parts, MOPS is used as a supporting electrolyte to balance the pH of the electrolyte, and NaCl provides sufficient chloride ions to react with the counter electrode silver wire.

[0032] Assemble the catheter:

[0033] The obtained Cu-BDC@CF catalyst was directly used as the working electrode, and a 0.1 mm Ag wire was selected as the counter electrode. Insulating tape was used to cover the surface of the Cu-BDC@CF catalyst and the Ag wire to ensure that the Cu-BDC@CF catalyst and the Ag wire in the catheter were electrically insulated from each other and a 3-5 cm long exposed area was left. The Cu-BDC@CF catalyst and the Ag wire were placed in the catheter, ensuring that one end could be connected to the electrode clamp outside the catheter. The above electrolyte was added to the catheter, and sealant was applied to both ends of the catheter.

[0034] Electrocatalytic reduction test:

[0035] Place the assembled catheter at the relevant part, and connect the leads of the working electrode and the counter electrode to an external power supply (workstation). Apply power at a voltage of 0 to -0.4 V for a certain period of time to produce an appropriate amount of NO. The NO produced then diffuses through the catheter wall to the relevant part, and acts on the blood cells or bacteria attached to the outer wall through a series of complex biochemical reactions to achieve an antibacterial effect.

[0036] The technical solution of the present invention has the following beneficial effects:

[0037] 1. The catalyst Cu-BDC@CF prepared by the method of the present invention is composed of Cu-MOF material and carbon fiber. The heat generation physical properties and mechanical strength of the base carbon fiber are utilized to realize the combination of heterogeneous electrocatalytic nitrite generation nitric oxide (NO) technology and medical catheters, which has the characteristics of low cost, high efficiency, high stability, and recyclability.

[0038] 2. The Cu-BDC@CF catalyst prepared by the method of the present invention exhibits catalytic performance for effective and controllable generation of NO, and the NO flux it produces can meet clinical needs.

[0039] 3. The catalyst preparation method is simple, does not require complex equipment, and has good commercial prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0041] Figure 1 This is the SEM image of the Cu-BDC@CF catalyst of Example 1;

[0042] Figure 2 This is a performance diagram of the Cu-BDC@CF catalyst in the electrocatalytic nitrite reduction reaction of Example 4;

[0043] Figure 3 This is the stability test diagram of Cu-BDC@CF catalyst;

[0044] Figure 4 This is a performance diagram of the application of Cu-BDC@CF catalyst in medical catheters according to Example 5;

[0045] Figure 5 This is a diagram showing the antibacterial effect of the Cu-BDC@CF catalyst in a medical catheter according to Example 6;

[0046] Figure 6 This is a performance diagram of the catalyst of Comparative Example 1 in the electrocatalytic nitrite reduction reaction;

[0047] Figure 7 This is a performance diagram of the catalyst of Comparative Example 2 used in a medical catheter. DETAILED DESCRIPTION

[0048] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0049] When the embodiments give numerical ranges, it should be understood that, unless otherwise specified in the present application, the two endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present application have the same meaning as those generally understood by those skilled in the art. In addition to the specific methods, equipment, and materials used in the embodiments, according to the grasp of the prior art by those skilled in the art and the record of the present application, any method, equipment, and material of the prior art similar or equivalent to the methods, equipment, and materials described in the embodiments of the present application can also be used to realize the present application.

[0050] It should be understood that the experimental methods used in the following examples are conventional methods unless otherwise specified, and the materials, reagents, etc. used in the following examples are all commercially available unless otherwise specified.

[0051] Example 1 Preparation of Cu-BDC@CF catalyst

[0052] Dissolve 7.0 mmol of CuSO4·5H2O in 25 mL of DMF to obtain a copper sulfate solution;

[0053] Dissolve 7.0 mmol of terephthalic acid in 25 mL of DMF to obtain a terephthalic acid solution;

[0054] First, transfer the terephthalic acid solution obtained above to a hydrothermal reactor, then carefully spread the copper salt solution slowly on the upper layer of the terephthalic acid solution, and heat at 105°C for 40h to obtain a blue precipitate;

[0055] The precipitate obtained above was washed with DMF and ethanol in sequence, and then dried in a vacuum drying oven to obtain Cu-BDC powder;

[0056] Weigh appropriate amounts of Cu-BDC powder, anhydrous ethanol, and Nafion (perfluorosulfonic acid polymer solution) solution to prepare an ethanol solution, the composition of which is 2 mg Cu-BDC and 40 μL Nafion per mL ethanol solution;

[0057] The cleaned carbon fiber (CF) was immersed in the above solution for 3 cm for 20 min, and then the immersed part was placed under an infrared lamp to dry to obtain the Cu-BDC@CF catalyst. The product morphology is shown in the attached manual. Figure 1 As shown, it can be seen that the Cu-BDC nanomaterials are attached to the carbon fibers.

[0058] Example 2 Preparation of Cu-BDC@CF catalyst

[0059] Dissolve 8.0 mmol of Cu(NO3)2·3H2O in 25 mL of DMF to obtain a copper nitrate solution;

[0060] 8.0 mmol of terephthalic acid was dissolved in 25 mL of DMF to obtain a terephthalic acid solution;

[0061] First, transfer the terephthalic acid solution obtained above to a hydrothermal reactor, then carefully spread the copper salt solution slowly on the upper layer of the terephthalic acid solution, and heat at 115°C for 30h to obtain a blue precipitate;

[0062] The precipitate obtained above was washed with DMF and ethanol in sequence, and then dried in a vacuum drying oven to obtain Cu-BDC powder;

[0063] Weigh appropriate amounts of Cu-BDC powder, anhydrous ethanol, and Nafion (perfluorosulfonic acid polymer solution) solution to prepare an ethanol solution, the composition of which is 4 mg Cu-BDC and 80 μL Nafion per mL ethanol solution;

[0064] The cleaned carbon fiber filaments were immersed in the above solution for 5 cm for 30 min, and then the immersed part was placed under an infrared baking lamp for drying to obtain the Cu-BDC@CF catalyst.

[0065] Example 3 Preparation of Cu-BDC@CF catalyst

[0066] Dissolve 7.5 mmol of Cu(NO3)2·3H2O in 25 mL of DMF to obtain a copper nitrate solution;

[0067] Dissolve 7.5 mmol of terephthalic acid in 25 mL of DMF to obtain a terephthalic acid solution;

[0068] First, transfer the terephthalic acid solution obtained above to a hydrothermal reactor, then carefully spread the copper salt solution slowly on the upper layer of the terephthalic acid solution, and heat at 120°C for 30h to obtain a blue precipitate;

[0069] The precipitate obtained above was washed with DMF and ethanol in sequence, and then dried in a vacuum drying oven to obtain Cu-BDC powder;

[0070] Weigh appropriate amounts of Cu-BDC powder, anhydrous ethanol, and Nafion (perfluorosulfonic acid polymer solution) solution to prepare an ethanol solution, the composition of which is 4 mg Cu-BDC and 80 μL Nafion per mL ethanol solution;

[0071] The cleaned 1×1 cm carbon fiber cloth was immersed in the above solution for 5 cm for 30 min, and then the immersed part was placed under an infrared baking lamp and dried to obtain the Cu-BDC@CF catalyst.

[0072] Its specific appearance is as follows Figure 1 shown.

[0073] Example 4 Application of Cu-BDC@CF catalyst in nitrite reduction reaction

[0074] The Cu-BDC@CF catalyst obtained in Example 3 was used as the working electrode, with a platinum electrode as the counter electrode, an Ag / AgCl electrode as the reference electrode, and a solution of 0.4M NaNO2, 0.5M MOPS buffer, and 0.2M NaCl as the electrolyte. The electrochemical performance of the synthesized Cu-BDC@CF catalyst was tested in an electrolytic cell under a three-electrode system. The applied potential range was between 0.66V and 0.26V (vs. Ag / AgCl), and each test lasted 2h. The volume of the gas phase in the electrolytic cell was about 40mL, and the attached Figure 2 From the performance data, it can be seen that the material has a relatively good Faradaic efficiency and considerable NO yield, showing relatively excellent nitrite reduction performance.

[0075] Afterwards, the cycle stability test was carried out under the condition of an applied voltage of 0.46V, which showed its excellent stability and proved its potential for further commercial application. The results are shown in the attached manual. Figure 3 shown.

[0076] Example 5 Application of Cu-BDC@CF catalyst in medical catheters

[0077] The material obtained in Example 1 was used as a working electrode and placed together with a 0.1 mm Ag wire in a medical catheter to form a dual-electrode system, wherein the catheter was made of silicone rubber, the catheter length was 8 cm, the catheter structure was a double-lumen structure (one end of one chamber was blocked and the other end was open as a drug delivery end), and the outer diameter of the catheter was 2 mm.

[0078] The electrolyte used was a solution containing 0.4 M NaNO2, 0.5 M MOPS buffer, and 0.2 M NaCl.

[0079] The applied voltages were 0V, -0.1V, -0.2V, -0.3V-0.4V, respectively, and the single duration was 2h. After NO diffusion was sufficient, the NO concentration in the sealed container was detected to calculate the NO flux generated by the catheter. The results met the needs of clinical application. The specific results are shown in the attached manual. Figure 4 As shown in the figure, the Cu-BDC@CF catalyst can generate 0.9~13.0×10-10 mol min -1 cm -2 The NO flux can be used for biological applications. It can fully cover the antibacterial and anticoagulant application range of NO, showing great commercial application value.

[0080] Example 6 Antibacterial effect of medical catheters prepared by Cu-BDC@CF catalyst

[0081] The Cu-BDC@CF catalyst, electrolyte and catheter in Example 5 were still used to conduct an experiment on antibacterial biofilm function. Escherichia coli was used as the experimental object.

[0082] Use the assembled catheter and place it at OD 600 =0.60 bacterial stock solution for 1 hour to allow the bacteria to adhere to the outer wall surface of the catheter. Then take out the catheter and put it back in a fresh liquid culture solution that does not contain bacteria to allow the bacteria attached to the outer wall of the catheter to grow into a film. The growth cycle is 48 hours, and the liquid culture solution needs to be replaced every 24 hours. Finally, connect the external electrochemical workstation to the electrodes in the catheter, turn on the workstation power, and apply a working voltage of -0.1V for 3 hours. This is the experimental group. At the same time, prepare another catheter that is not connected to the external electrochemical workstation and immerse it in a bioreactor with exactly the same composition conditions. This is the control group.

[0083] After the experiment, the catheter was removed, and the outer surface of the catheter was gently rinsed with phosphate buffer (1×PBS), and then placed in phosphate buffer for homogenization to transfer the bacteria attached to the catheter surface to the phosphate buffer to obtain a bacterial suspension. The obtained bacterial suspension was analyzed to investigate the specific antibacterial effect of this method.

[0084] Specifically, after appropriate dilution multiples, 50 μL of the diluted bacterial suspension was placed on a solid agar plate, spread evenly, and placed in a 37°C incubator for overnight culture to obtain the attached Figure 5 The agar plate of the control group (left) was covered with bacterial colonies after a night of growth, while the agar plate of the experimental group (right) was empty, showing an excellent antibacterial effect.

[0085] In summary, the Cu-BDC@CF catalyst prepared in the examples of the present application exhibits relatively excellent nitrite reduction performance and antibacterial properties.

[0086] Comparative Example 1 Application of CF catalyst in nitrite reduction reaction

[0087] The electrochemical performance of the CF catalyst was tested in an electrolytic cell under a three-electrode system using CF as the working electrode, a platinum electrode as the counter electrode, an Ag / AgCl electrode as the reference electrode, and a solution of 0.4M NaNO2, 0.5M MOPS buffer, and 0.2M NaCl as the electrolyte. The applied potential range was between 0.66V and 0.26V (vs. Ag / AgCl), and each test lasted 2h. The results are shown in the attached figure. Figure 6 From the performance data, it can be seen that the NO generation rate of this material is greatly reduced compared with the Cu-BDC@CF catalyst.

[0088] Comparative Example 2 Application of CF Catalyst in Medical Catheters

[0089] CF was directly used as the working electrode and placed in a medical catheter together with a 0.1 mm Ag wire to form a dual-electrode system. The catheter was made of silicone rubber, was 8 cm long, had a double-lumen structure (one end of one chamber was blocked and the other end was open as the drug delivery end), and had an outer diameter of 2 mm.

[0090] The electrolyte used was a solution containing 0.4 M NaNO2, 0.5 M MOPS buffer, and 0.2 M NaCl.

[0091] The applied voltages were 0V, -0.1V, -0.2V, -0.3V-0.4V, respectively, and the single duration was 2h. After NO diffusion was sufficient, the NO concentration in the sealed container was detected to calculate the NO flux generated by the catheter. The specific results are shown in the attached manual. Figure 7 As shown, similarly, compared with the Cu-BDC@CF catalyst, the NO flux of this material is greatly reduced and cannot meet the needs of medical applications at all. It also reflects the effectiveness of the Cu-BDC@CF catalyst of the present invention.

[0092] The foregoing examples are merely illustrative and are used to explain some features of the method of the present invention. The appended claims are intended to claim the widest possible range that can be conceived, and the embodiments presented herein are only illustrations of selected implementations according to the combination of all possible embodiments. Therefore, it is the applicant's intention that the appended claims are not limited by the selection of examples that illustrate the features of the present invention. Some numerical ranges used in the claims also include sub-ranges within them, and changes in these ranges should also be interpreted as being covered by the appended claims where possible.

Claims

1. An application of a Cu-BDC@CF catalyst in preparing NO by electrocatalytic reduction reaction, characterized in that: The preparation method includes the following contents: The carbon fiber is immersed in a mixed solution of Cu-BDC and Nafion for 10-30 min, and then the immersed part is dried to obtain a Cu-BDC@CF catalyst, wherein the Cu-BDC is attached to the carbon fiber; wherein the concentration of the Cu-BDC solution is 1-4 mg / mL, and the concentration of the Nafion is 20-80 μL / mL; The Cu-BDC solution is obtained by dissolving Cu-BDC powder in a solvent; Cu-BDC powder is prepared by the following method: transferring the terephthalic acid solution to a hydrothermal reactor, then spreading the copper salt solution on the upper layer of the terephthalic acid solution and heating it to obtain a blue precipitate, washing and drying it; Heating conditions are 100~130℃, 30~40h; Furthermore, the obtained blue precipitate was washed with DMF and ethanol in sequence.

2. The use of the Cu-BDC@CF catalyst according to claim 1, characterized in that: The copper salt is selected from one or more of Cu(NO3)2·3H2O, CuSO4·5H2O and copper chloride.

3. The use of the Cu-BDC@CF catalyst according to claim 1, characterized in that: The method also includes a pretreatment step of the carbon fiber, specifically, placing the carbon fiber in a 0.1-1.0 mol / L hydrochloric acid solution for ultrasonic treatment, then placing the carbon fiber in acetone for ultrasonic treatment, and then washing with distilled water and / or ethanol; Furthermore, the carbon fiber is carbon fiber cloth or carbon fiber filament; further, the specification of the carbon fiber cloth is (0.5~2) cm×(0.5~2) cm.

Citation Information

Patent Citations

  • Fluorescent sensor for detecting inorganic pyophosphatase and its preparation method

    CN108051418A

  • Cu-MOFs-supported porous fibrous scaffold material and preparation method and application thereof

    CN111388753A

  • Biocompatible materials for medical devices

    US20110159116A1